Pengembangan Media Komik sebagai Hasil Alih Wahana Cerita Rakyat Kabupaten Ogan Komering Ilir melalui Aplikasi Canva - Julia, Nita; Ansori, Ansori; Nuzula, Khalidatun (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study aims to develop comic media as a result of the transfer of the folklore of the History of Teluk Gelam Lake, Ogan Komering Ilir Regency through the Canva application in class X at MAS Darussalam Lempuing Ogan Komering Ilir. This study uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate) but this study was only carried out up to the Develop stage, without continuing to the Disseminate stage. The product was developed based on a needs analysis obtained through questionnaires and interviews with students and teachers. The results of the analysis indicate that Canva-based comic media is needed as a learning tool. The learning media design stage begins with writing a script, making a flowchart, and a storyboard as the initial framework for developing comic media. The development stage is carried out using the Canva application to produce comic media that is in accordance with learning needs. Expert validation is carried out on aspects of material, media, and language. Based on the feasibility test that has been carried out by experts, this product as a whole is declared very feasible. In terms of material, the percentage of feasibility is 94.4% with a very feasible category. The media aspect obtained 93.7% with a very feasible category, and the language aspect obtained 85.7% with a very feasible category. Product revisions were carried out according to the suggestions of the validator. With these results, Canva-based comic media was declared very feasible to be used as a learning medium. The development of comic media as a result of the transfer of the historical folklore of Lake Teluk Gelam through the Canva application is expected to be developed and continued to the final stage. This comic-based learning media needs to be tested on students and teachers to assess its effectiveness in supporting the learning process and the achievement of learning objectives. This is important because this study only reached the expert validation and product revision stages. Therefore, additional testing is needed to ensure that this comic media is effective and the validity of this comic media in improving students' understanding of the material presented.